The Brazilian credit market for small and medium-sized firms: an adaptive marketing approach - Zambaldi, Felipe (2007)
In this work, the Brazilian credit market for small and medium-sized enterprises (SMEs) is analyzed from an adaptive marketing perspective, in which marketing activities such as segmentation, customer relationship management, pricing and product development are determined by the utility that market players get when they satisfy the demand. The existence of information asymmetry and transaction costs is identified to limit and drive marketing initiatives in the studied credit market. From a sample of 65,535 credit proposals analyzed by a large Brazilian bank from January 2004 to September 2006, the bank’s utility in a credit transaction is studied. Additionally, 17,149 credit transactions provided by the bank to the small business segment from April 2006 to March 2007 are investigated. Finally, a data set with 1,636 registers, obtained from the merge of the mentioned samples of proposals and transactions, is investigated in terms of the relations between interest rates and the collateral committed in credit proposals. The results reveal the existence of an adaptive marketing environment, in which small business borrowers are credit rationed and accept to pay higher interest rates than other segments. Credit products based on liquid collateral and high interest rates are designed to opportunistically supply this rationed small business segment. Also, the bank’s utility from a credit transaction is affected by the private information it captures along its relationships with customers. Findings imply that the Brazilian financial marketing system does not perform a formative function in economic development, which would be to foster the demand for productive credit by means of low-priced loans to small and medium-sized enterprises. However, a formative marketing system is not likely to occur in an environment characterized by imperfect information, like the Brazilian credit market. This study provides relevant information to those who are interested in the development of productive credit markets, like professionals of financial institutions; public and monetary policy makers; and small and medium-sized business entrepreneurs whose businesses face the need for external funding.